Resilience Process of Economically Disadvantaged Households with School Children in COVID-19-Induced Remote Learning - Lagat, Kevin T.; Nuñez, Lilian B.; Galgo, Christopher Jr. R.; Yap, Karen Luz P. (Philippine Social Science Journal, 2023)
Resilience amid COVID-19-induced remote learning difficulties is disproportionate for disadvantaged families due to structural inequalities. This paper investigated the resilience process of economically disadvantaged households by examining how they mediate responses to the challenges in COVID-19-induced remote learning. Utilizing a case study research design, 15 purposely selected households from Naval, Biliran, with children enrolled in remote education and monthly income below the poverty threshold, were interviewed using an interview guide, and their narratives were thematically analyzed. Results revealed that households mobilized their available resources to minimize the difficulties in COVID-19-induced remote learning. However, in the process, risks are shifted to their consumption, productive work and livelihood, parents’ health, and children’s learning. In the end, the resilience process of households was characterized by the management of time and capital and unsustainability. This paper argues that increased community and government support is needed for sustainable household implementation of remote learning.